UNSUR BUDAYA MINANGKABAU DALAM NOVEL MENCARI CINTA YANG HILANG KARYA ABDULKARIM KHIARATULLAH - Irawati, Diah (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2015)
This research aims to describe (1) function of "maternal uncle" for his nephew (2) prohibition for the same tribe marriage (3) the function of maternal uncles for people in one tribe including in Novel "Mencari cinta yang Hilang" by Abdulkarim Khiaratullah. This research was qualitative research that used descriptive methode which had characteristic was conten analysis, that is a research which have done by examining a literature manuscript by looking at a piece of fact or dialog from the figure that purpose to knowing the element of minangkabau culture that including in novel. Technique of gathering data in this research use documentation technique and writing a note technique. Analysis result show that, first, in overal 'maternal uncle' describing in this novel is responsive and guiding his nephew, its according to rules, which 'maternal uncle' in Minangkabau People is very important to his nephew life. Only 'maternal uncle' from Rahima, Mak Katik which did not a right job. Second, problem about forbidding one tribe marriage is still a trouble on Minangkabau people life, that is reflected in novel that still find a polemic about forbidding one tribe wedding, tradition agreement which very compoting with one tribe marriage whom judging as marriage with own family, in other hand based on religion one tribe marriage is not forbidden thing. Third, this novel also reflect a figure of 'Niniak Mamak' in minangkabau people, there is finish tradition clash, in this novel 'niniak mamak' also finish a problem of one tribe marriage, which is Chaniago clan, on discussion which leading by Datuk Rangkayo Sati as people leader has a decision which a one tribe marriage between Fauzi and Rahima can not continued.